ANALISIS DISTRIBUSI PERJALANAN MENGGUNAKAN MODEL GRAVITASI DUA BATASAN DENGAN OPTIMASI FUNGSI HAMBATAN STUDI KASUS : KOTA SEMARANG DAN KOTA SURAKARTA - Novianna Dwi Pramesti; Wahyu Laras Wulandari; Bambang Riyanto; Kami Hari Basuki (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Movement patterns in the region are caused by the interaction of traffic flow in the activity pass. If a region has a large enough population density, the greater the movement of traffic generated. It usually occurs in cities that are growing, such as the city of Semarang and Surakarta. To minimize the number of transportation problems arising from the interaction of traffic flow, it is necessary transportation plans an efforts as early as possible. This study aimed to determine the pattern of movement by using two restriction Gravity Model (rise and pull). Required data is secondary data, such as the distance between the zones, travel time, the amount of land area in a zone and productive age among 15-59 years. Linear regression analysis is used to get the Origin Destination Matrix. From linear regression analysis can be known the variable that affects movement patterns. It can be concluded from the results of this study that Surakarta city are more sensitive in comparison to Semarang City in distance. Therefore, it can be said that the town of Surakarta is more environmentally friendly because fuel consumption needed by society is not high compared with the city of Semarang.